Hyperuricemia in Patients Taking Anti-Tuberculosis Drugs Including Pyrazinamide for both Category-1 and Category-2 Tuberculosis, in Population of KPK-Pakistan (Medical Forum Monthly, 2024)
Objective: To document hyperuricemia in patients taking Anti-Tuberculosis Therapy (ATT) including Pyrazinamide (PZA) in both CAT-1 and CAT-2 Patients.Study Design: An open labeled & single centered longitudinal study.Place and Duration of Study: This study was conducted at the Khyber Medical College (KMC) & Khyber Teaching Hospital, Peshawar from December 2016 to May 2017.Materials and Methods: Sixty patients with pulmonary tuberculosis were enrolled. Patients were assigned into 2-groups (30 patients in each group), including group-A as CAT-1 patients, who were taking ATT for the first time and group-B as CAT-2, who presented with recurrent tuberculosis and were put on ATT for the second time. Standard ATT was given to group-A and Streptomycin was added to standard ATT in group-B for the first 02-months and uric acid (UA) level was done before the initiation of therapy, at the end of two-month intensive regimen and 02-months after the stopping Pyrazinamide. The primary target was to find out hyperuricemia in both groups.Results: In CAT-1 patients, uric acid was increased to 6.44 ± 0.91 after two months aggressive regimen, and with discontinuation of pyrazinamide in CAT-1 patients for two month the uric acid falls again to 4.71 ± 0.83. Similarly, in CAT-2 patients, uric acid was increased to 6.64 ± 0.91 with two months therapy which downgrade to 5 ± 1.15 after two months of stopping pyrazinamide. There is significantly increase in uric acid level with two months of ATT in both groups (p-value=0.01). There is 100% recovery in female patient in Cat-1 as compared to Cat-2 female patients (91.6%), similarly 94.77% males improved in Cat-1 as compared to Cat-2 males whose recovery is 86.67%.Conclusion: ATT including PZA can cause significant hyperuricemia, in both CAT-1 and CAT-2 patients. This raised in uric acid level is reversible with discontinuation of PZA, but may persist in some of CAT-2 patients.